Modeling the impact of entrepreneurial attitude on self-employment intention among engineering students in Ethiopia - Mesfin Mulu Ayalew; Shumet Amare Zeleke (Journal of Innovation and Entrepreneurship, 2018)
Entrepreneurship is a worldwide phenomenon with economic growth across the globe that is rendered by the emergence of new and innovative business start-ups. Thus, the main objective of this research was to model the impact of entrepreneurial attitudes on self-employment intention among final year engineering students in Bahir Dar Institute of Technology, Debre Markos University and University of Gondar, Ethiopia, in 2017. To achieve the objective of the study, a survey research approach was employed. Questionnaire and interview were the instruments used, and stratified sampling technique was adopted to select 921 respondents from a population of 4327 final year undergraduate engineering students in 2016/2017 academic session. To analyze the data, descriptive statistics, chi-square test, principal component factor analysis, and binary logistic regression analysis were employed. The descriptive result revealed that about 57.4% of the students had an intention to be self-employed while 42.6% do not have an intention. The principal component factor analysis was used to reduce the set of variables by grouping variables with similar characteristics together and generates new variables (factors). These methods help the researchers to transform the number of correlated variables into a smaller number of uncorrelated variables. The logistic regression analysis was performed to investigate the effect of the predictor variables on self-employment intention status of students. The results showed that entrepreneurial education/training and entrepreneurial attitudes significantly predicts students' self-employment intention. Accordingly, information and opportunity seeking, creativity and problem solving skills, achievement and instrumental readiness, self-confidence and self-esteem, goal setting, entrepreneurship education/training, business-owned family background, prior business experience with family, access to finance/capitals for startup, and networking and professional contacts were found to be significant predictors at 5% level of significance. These factors had positive relationship with self-employment intention at 5% level of significance. In the meanwhile, demographic factors (such as age, gender, and marital status) and socio-economic factors (such as parents' occupation, colleagues' business background, means of finance, discouragement by external environment, and clear future business idea) are not significant predictors at 5% level of significance. The study recommends that the government as well as the universities should design programs that facilitate entrepreneurship to change the mindset, attitude, and intention of those students who do not have knowhow about entrepreneurship as a future career.
Keywords: 650; Entrepreneurial attitude; Self-employment intention; Principal component analysis; Binary logit model; Student